SYSTEM OF WORK IN STATE ORGANIZATIONS AND ITS ECONOMIC ESSENCE - Ergashov Israil Hasanovich; T.I. Bobokulov (Scholar Express Journals, 2022)
In this article, the system of working in state organizations is analyzed, besides, the economic significance of these processes is considered
Keywords: administration; information; management body